Association of dry eye syndrome with oral Isotretinoin therapy for severe nodulocystic acne and recalcitrant acne vulgaris - Amatya, Amit; Sharma, Ranjana; Karn, Dharmendra Kumar; Kaiti, Raju (Journal of Patan Academy of Health Sciences, 2015)
Introduction: Oral isotretinoin was registered in Nepal almost three decades later its first introduction in USA. It remains the most clinically effective medication for acne. Dry eye syndrome is a ‘certain’ adverse effect of oral isotretinoin therapy which can be validated by tear film break up time and Schirmer I tests.Methods: Fifty patients aged above 12 years presenting to dermatology outpatient department of Dhulikhel Hospital with severe nodulocystic acne or recalcitrant acne vulgaris not responding to three months of systemic antibiotics along with topical agents were included. Tear film break up time and Schirmer I tests before, at 45 and 90 days, and one month after taking oral isotretinoin were performed to study association of dry eye syndrome due to oral isotretinoin.Results: Both eyes of fifty selected patients were sampled. Baseline mean tear film break up time of 12.37±4.17 sec decreased to 9.69±3.70 sec, 9.09±3.77 sec and 10.67±3.50 sec at 45 and 90 days and on follow up, respectively. Likewise, baseline mean Schirmer I value of 16.68±8.73 mm decreased to 12.26±7.64 mm, 11.49±8.07 mm and 11.76±8.11 mm respectively at 45 and 90 days and on follow up. The differences between the mean values were analyzed using paired samples T test and all were statistically significant except between the mean Schirmer values at 90 days and on follow up.Conclusions: Abnormal mean tear break up time at 45 and 90 days in this study suggests that dry eye syndrome was caused by oral isotretinoin during acne therapy but tends to revert to normal on cessation.Journal of Patan Academy of Health Sciences, Vol. 2, No. 1, 2015. page:12-16